2022
DOI: 10.1002/cssc.202201662
|View full text |Cite
|
Sign up to set email alerts
|

Divergent C−H Amidations and Imidations by Tuning Electrochemical Reaction Potentials

Abstract: Electrochemical C−H functionalizations are attractive transformations, as they are capable of avoiding the use of transition metals, pre‐oxidized precursors, or suprastoichiometric amounts of terminal oxidants. Herein an electrochemically tunable method was developed that enabled the divergent formation of cyclic amines or imines by applying different reaction potentials. Detailed cyclic voltammetry analyses, coupled with chronopotentiometry experiments, were carried out to provide insight into the mechanism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Carbon cations could be attacked by primary amines instead of the secondary amines mentioned above after electrooxidation. In the approach by Schomaker, 40 primary sulfonyl amine 13 was used instead of secondary amine 9 described above, and C–H oxidative amination was still achievable electrochemically (Scheme 6). In the initial reaction stage, electron-rich benzene in 13 was readily oxidized to the corresponding radical cation 13A , which would form benzyl radical 13B by deprotonation.…”
Section: C–h Bond Electrochemical Aminationmentioning
confidence: 99%
“…Carbon cations could be attacked by primary amines instead of the secondary amines mentioned above after electrooxidation. In the approach by Schomaker, 40 primary sulfonyl amine 13 was used instead of secondary amine 9 described above, and C–H oxidative amination was still achievable electrochemically (Scheme 6). In the initial reaction stage, electron-rich benzene in 13 was readily oxidized to the corresponding radical cation 13A , which would form benzyl radical 13B by deprotonation.…”
Section: C–h Bond Electrochemical Aminationmentioning
confidence: 99%
“…Moreover, we also disclosed an electrochemical C­(sp 3 )-H amidation with the mediation of anodically generated nitrogen-centered radicals. As a part of our continuous interests in synthetic electrochemistry, we herein reported that anodically generated oxygen-centered radicals served as hydrogen-atom transfer (HAT) mediators to promote benzylic C­(sp 3 )-H imidation (Scheme c) . Interestingly, this protocol provides a complementary approach to accessing different chemoselectivity compared to the previous reports.…”
Section: Introductionmentioning
confidence: 99%